Magic in the weave - Clare, Alys (Clare, Alys. Gabriel Taverner series, 2022)
"October, 1604. Plague has hit London, and the theatres are closed. But the capital's loss is Plymouth's gain, when a London theatre troupe, the Company, arrive on their 'Plague Tour'. Country physician Gabriel Taverner is both bewitched and unnerved by the Company's sexually charged staging of Othello. The play thrums with magic and witchcraft - perilous subjects, with the King's deadly spies lurking around every corner. When Gabriel's good friend, Coroner Theophilus Davey, tells him of a dangerous, whispered conversation overheard during a brief break, suggesting one of the cast fled London in possession of a terrible secret, Gabriel is even more relieved the Company will soon be on their way. But then one of the actors collapses, and Gabriel finds himself caught in a waking nightmare, where nothing is as it appears. Death is stalking the Company - but how can Gabriel hope to catch a cold-blooded killer, if he can't even trust the evidence of his own eyes?"--Jacket